Oxidative degradation of bilirubin produces vasoactive compounds. - Kranc, K; Pyne, G; Tao, L; Claridge, T; Harris, D; Cadoux-Hudson, T; Turnbull, J; Schofield, C; Clark, J (2000)
Subarachnoid haemorrhage is often followed by haemolysis and concomitant oxidative stress, and is frequently complicated by pathological vasoconstriction or cerebral vasospasm. It is known that upregulation of haem oxygenase (HO-1) is induced by oxidative stress and results in release of biliverdin and bilirubin (BR), which are scavengers of reactive oxygen species (ROS). Here we report biomimetic studies aimed at modelling pathological conditions leading to oxidative degradation of BR. Oxidative degradation products of BR, formed by reaction with hydrogen peroxide (an ROS model system), demonstrated biological activity by stimulating oxygen consumption and force development in vascular smooth muscle from porcine carotid artery. Analogous biological activity was observed with vasoactive cerebrospinal fluid from subarachnoid haemorrhage patients. Three degradation products of BR were isolated: two were assigned as isomeric monopyrrole (C9H11N2O2) derivatives, 4-methyl-5-oxo-3-vinyl-(1, 5-dihydropyrrol-2-ylidene)acetamide and 3-methyl-5-oxo-4-vinyl-(1, 5-dihydropyrrol-2-ylidene)acetamide and the third was 4-methyl-3-vinylmaleimide (MVM), a previously isolated photodegradation product of biliverdin. Possible mechanisms of oxidative degradation of BR are discussed. Tentative assignment of these structures in the cerebrospinal fluid (CSF) of cerebral vasospasm patients has been made. It is proposed that one or more of the degradation products of biliverdin or bilirubin are involved in complications such as vasospasm and or pathological vasoconstriction associated with haemorrhage.